Passing interest : racial passing in US novels, memoirs, television, and film, 1990-2010 - Nerad, Julie, 1969- (SUNY Press, 2014)
"The first volume to focus on the trope of racial passing in novels, memoirs, television, and films published or produced between 1990 and 2010, Passing Interest takes the scholarly conversation on passing into the twenty-first century. With contributors working in the fields of African American studies, American studies, cultural studies, film studies, literature, and media studies, this book offers a rich, interdisciplinary survey of critical approaches to a broad range of contemporary passing texts. Contributors frame recent passing texts with a wide array of cultural discourses, including immigration law, the Post-Soul Aesthetic, contemporary political satire, affirmative action, the paradoxes of "colorblindness," and the rhetoric of "post-racialism"-- Back cover
Keywords: Andrae, A.; Bibel -- Philemonbrief; Universidad Sergio Arboleda; American literature -- 20th century -- History and criticism.; American literature -- 21st century -- History and criticism.; Passing (Identity) -- United States -- History -- 20th century.; Passing (Identity) -- United States -- History -- 21st century.; Passing (Identity) in literature.; Passing (Identity) in motion pictures.; Race in literature.; Race in motion pictures.; Littérature américaine -- 20e siècle -- Histoire et critique.; Littérature américaine -- 21e siècle -- Histoire et critique.; Passing (Identité) -- États-Unis -- Histoire -- 20e siècle.; Passing (Identité) -- États-Unis -- Histoire -- 21e siècle.; Passing (Identité) dans la littérature.; Race dans la littérature.; Race au cinéma.; LITERARY CRITICISM -- American -- General.; American literature; Passing (Identity); Passing (Identity) in literature; Passing (Identity) in motion pictures; Race in literature; Race in motion pictures; United States; Autobiografie; Amerikanisches Englisch; Fernsehsendung; Rasse -- Motiv; Verwechslung -- Motiv; LITERARY CRITICISM / American / General; 1900-2099; Criticism, interpretation, etc.; History